(untitled) (Journal of Indonesian Legal Studies, 2026)
This study examines the implications of Constitutional Court Decision No. 199/PUU-XXIII/2025, which affirms the constitutionality of the interim replacement (Pergantian Antarwaktu/PAW) of members of the House of Representatives (DPR) at the initiative of political parties. It focuses on whether the Court’s interpretation of Article 22E paragraph (3) of UUD NRI 1945 is consistent with the principle of popular sovereignty and whether party-initiated recall remains constitutionally justified within an open-list proportional electoral system based on candidates’ highest vote totals. This study employs a legal research methodology using statutory, conceptual, and case approaches, examining the UUD NRI 1945, Law Number 17 of 2014, Law Number 2 of 2011, Law Number 7 of 2017, and relevant Constitutional Court decisions. The study argues that Decision No. 199/PUU-XXIII/2025 reinforces party sovereignty by relying on and repeating the reasoning of Decision No. 38/PUU-VIII/2010 without adequately rethinking the constitutional implications of the contemporary electoral system. Such jurisprudential repetition shifts control over the representative mandate from voters to political parties, weakens vertical accountability to constituents, and undermines the legitimacy of individual votes. The decision therefore risks transforming Indonesian representative democracy from a people-centered model into a party-centered electoral model, in which popular sovereignty is formally preserved but substantively weakened